Alkaline dry battery

By using various types of zinc alloy particles in alkaline dry batteries and controlling the oxygen content rate, the problem of temperature rise during external short circuit is solved, and the safety of the battery is significantly improved.

CN119234331APending Publication Date: 2024-12-31PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041613.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-24
Filing Date
2023-05-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The temperature rises too much when the alkaline dry battery is short-circuited externally, which affects safety and is difficult to effectively suppress the existing technology.

Method used

The zinc alloy powder is used as the negative electrode active substance. The zinc alloy powder consists of three types of particles: the first zinc alloy particles with pores, the second zinc alloy particles without pores but with closed holes, the third one without pores and closed holes The zinc alloy particles have an oxygen content range of 400 to 1000 ppm, and the temperature rise is suppressed by appropriate proportion and average particle size control.

Benefits of technology

It significantly suppresses the temperature rise during external short circuit and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234331A_ABST
    Figure CN119234331A_ABST
Patent Text Reader

Abstract

The disclosed alkaline dry battery (10) comprises a negative electrode (3), and the negative electrode (3) comprises a zinc alloy powder. The zinc alloy powder includes first, second, and third zinc alloy particles. In a cross-sectional image of the zinc alloy powder, the first zinc alloy particles have specific pores (H), the second zinc alloy particles do not have pores (H) and have specific closed pores (V) therein, and the third zinc alloy particles do not have pores (H) and have no pores (V) therein. The hole H is a hole in which the ratio D / W of the linear distance D from the opening to the bottom surface to the width W of the opening is 1.0 or more, and the linear distance D is 2 [mu] m or more. The hole V is a hole having a minor diameter of 2 [mu] m or more. The oxygen content of the zinc alloy powder is within the range of 400-1000 ppm by mass ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to alkaline dry cell batteries. Background Art

[0002] Alkaline dry batteries (alkaline manganese dry batteries) have a larger capacity and can draw a larger current than manganese dry batteries, and therefore are widely used. Various zinc particles and zinc alloy particles have been proposed as negative electrode active materials for alkaline dry batteries.

[0003] Patent document 1 (Japanese Patent Application Laid-Open No. 2015-106449) discloses “a zinc alloy powder for alkaline batteries, characterized in that the zinc alloy powder has a bulk density of 3.0 or more and an oxygen concentration of 0.04 mass % or more and less than 0.10 mass %”.

[0004] Patent document 2 (Japanese Patent Application Laid-Open No. 60-56367) discloses "an alkaline battery characterized in that, in an alkaline battery using zinc powder as a negative electrode active material, at least a portion of the zinc powder is formed of zinc powder having pores in particles."

[0005] Patent document 3 (International Publication No. 2006 / 122628) discloses "an alloyed zinc powder for alkaline batteries, comprising one or more of 10 count % of a sieve fraction of -250 to 425 μm; 3 count % of a sieve fraction of -150 to 250 μm; and 2 count % of a sieve fraction of -105 to 150 μm, and having at least one hole therethrough."

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-106449

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 60-56367

[0010] Patent Document 3: International Publication No. 2006 / 122628 Summary of the invention

[0011] Problem that the invention aims to solve

[0012] In alkaline dry batteries, it is required to further improve safety by suppressing the temperature rise during an external short circuit. Under such circumstances, one object of the present disclosure is to provide an alkaline dry battery with a small temperature rise during an external short circuit.

[0013] Solutions for solving problems

[0014] One aspect of the present disclosure relates to an alkaline dry battery. The alkaline dry battery comprises: a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the negative electrode comprises a zinc alloy powder, the zinc alloy powder comprises a first zinc alloy particle, a second zinc alloy particle, and a third zinc alloy particle, in a cross-sectional image of the zinc alloy powder, the first zinc alloy particle is a particle having specific pores, the second zinc alloy particle is a particle having no specific pores and having specific closed holes inside, the third zinc alloy particle is a particle having no specific pores and having no specific closed holes inside, the specific pores are pores in which the ratio D / W of the straight-line distance D from the opening to the bottom surface to the width W of the opening is 1.0 or more, and the straight-line distance D is 2 μm or more, the specific closed holes are holes with a short diameter of 2 μm or more, and the oxygen content of the zinc alloy powder is in the range of 400 to 1000 ppm by mass ratio.

[0015] Effects of the Invention

[0016] According to the present disclosure, it is possible to suppress a temperature rise in an alkaline dry battery when an external short circuit occurs.

[0017] The novel features of the present invention are described in the appended claims, but the present invention, both in terms of configuration and content, together with other objects and features of the present invention, will be better understood from the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1A It is a schematic diagram for explaining the classification method of zinc alloy powder.

[0019] Figure 1B Another schematic diagram for explaining the classification method of zinc alloy powder.

[0020] Figure 2 This is a front view showing a part of the alkaline dry battery in one embodiment of the present disclosure as a cross section. DETAILED DESCRIPTION

[0021] Hereinafter, the embodiments of the present disclosure are described by giving examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials are sometimes exemplified, but other numerical values ​​and other materials may also be applied as long as the invention of the present disclosure can be implemented. In this specification, the so-called "numerical value A to numerical value B" may include numerical value A and numerical value B being replaced and read as "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values ​​involving specific physical properties, conditions, etc. are exemplified, any of the exemplified lower limits and any of the exemplified upper limits may be arbitrarily combined as long as the lower limit is not above the upper limit.

[0022] (Alkaline dry cell)

[0023] Hereinafter, the alkaline dry battery of the present embodiment may be referred to as “alkaline dry battery (A)”. The alkaline dry battery (A) includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The negative electrode includes zinc alloy powder.

[0024] The zinc alloy powder includes a first zinc alloy particle, a second zinc alloy particle, and a third zinc alloy particle. In the cross-sectional image of the zinc alloy powder, the zinc alloy powder is classified as follows. (1) The first zinc alloy particle is a particle having a specific hole (hereinafter sometimes referred to as "hole H"). The specific hole H is a hole in which the ratio D / W of the straight line distance D from the opening to the bottom surface to the width W of the opening is greater than 1.0, and the straight line distance D is greater than 2 μm.

[0025] (2) The second zinc alloy particles are particles that do not have specific pores H but have specific closed voids (hereinafter sometimes referred to as "specific voids V" or "voids V") inside. The specific voids V are voids having a minor diameter of 2 μm or more.

[0026] (3) The third zinc alloy particles are particles that do not have the specific pores H and do not have the specific voids V inside.

[0027] The oxygen content of the zinc alloy powder (hereinafter sometimes referred to as "oxygen content R") is in the range of 400 to 1000 ppm in terms of mass ratio. The oxygen content R is calculated according to the following formula.

[0028] Oxygen content R = (mass of oxygen in zinc alloy powder) / (mass of zinc alloy powder)

[0029] The oxygen content R of the zinc alloy powder can be measured by a general gas composition analysis method (Instrumental Gas Analysis: IGA).

[0030] Hereinafter, the first zinc alloy particle, the second zinc alloy particle, and the third zinc alloy particle are sometimes referred to as the "first particle", "the second particle", and the "third particle", respectively. It should be noted that the state of the zinc alloy powder changes as the battery is used. The evaluation results of the zinc alloy powder in this specification (the ratio of the first to third particles, the average particle size, the oxygen content R, etc.) refer to the evaluation results of the zinc alloy powder in the state before the battery is used. Examples of the zinc alloy powder in the state before the battery is used include: zinc alloy powder before being used for the negative electrode, and zinc alloy powder contained in the negative electrode of the battery before use.

[0031] When an alkaline dry cell battery is short-circuited externally, that is, when the positive terminal and the negative terminal of the alkaline dry cell battery are short-circuited outside the battery, a large current flows through the battery, and the battery temperature rises. Therefore, in order to improve the safety of the battery, it is required to suppress the temperature rise of the battery when the battery is short-circuited externally.

[0032] As a result of the research, the inventors of the present application have newly discovered that the temperature rise during an external short circuit can be significantly suppressed by mixing a plurality of zinc alloy particles of different shapes so that the oxygen content R falls within a predetermined range and using them as a negative electrode active material. The alkaline dry battery (A) disclosed herein is based on this new finding.

[0033] The reason why the temperature rise of the battery during an external short circuit can be suppressed according to the structure of the alkaline dry battery (A) is not clear at present, but it can be considered as follows.

[0034] The first particle (first zinc alloy particle) has a hole H, so it has a large specific surface area and high reactivity. Therefore, when an external short circuit occurs, the first particle reacts rapidly just after the short circuit, increasing the short circuit current. Therefore, if the proportion of the first particle is too high, a large current is generated, and the temperature rise of the battery at the beginning of the short circuit becomes larger. On the other hand, when there are a small amount of the first particle, a large current flows during an external short circuit, but the passivation of the zinc alloy powder is promoted, so the voltage drop and the temperature rise of the battery stop faster, and as a result, the excessive rise of the battery temperature can be suppressed. The second particle (second zinc alloy particle) does not have a hole H on the surface, so it does not react rapidly just after the short circuit. In addition, the second particle contains a hole V inside, so when there are a small amount of the second particle, the heat release during the external short circuit can be suppressed compared to the third particle without a hole V. However, when the second particle is consumed due to a short circuit, the internal hole V appears on the surface, the specific surface area becomes locally larger, and the reaction occurs rapidly. Therefore, if the ratio of the second particles is too high, the short-circuit current becomes difficult to decrease, and as a result, the generated heat is accumulated, and the battery temperature continues to rise.

[0035] From the above, it is believed that when the first to third particles exist in an appropriate ratio, it is effective to suppress the increase in battery temperature during external short circuit. The oxygen content R reflects the amount of natural oxide film on the surface of the zinc alloy particles. There is a tendency that the oxygen content of the first particle having holes H on the surface and the oxygen content of the second particle having holes V inside become higher than the oxygen content of the third particle. This is because if there are holes H, a zinc oxide film is also formed on the increased surface, and the oxygen content of the powder as a whole increases. In addition, if there are holes V, there is oxygen in the holes, and accordingly, the oxygen content of the powder as a whole increases. Therefore, by making the oxygen content R of the zinc alloy powder in the range of 400 to 1000 ppm (mass ratio), the first to third particles exist in an appropriate ratio, and as a result, there is a possibility that the increase in battery temperature during external short circuit is suppressed.

[0036] The oxygen content R of the zinc alloy powder is 400ppm or more, and may be 500ppm or more, 600ppm or more, or 700ppm or more. The oxygen content R is 1000ppm or less, and may be 900ppm or less, 850ppm or less, 750ppm or less, or 700ppm or less. The oxygen content R is in the range of 400 to 1000ppm, and may be in the range of 500 to 1000ppm, 600 to 1000ppm, or 700 to 1000ppm. In any of these ranges, as long as the lower limit is not greater than the upper limit, the upper limit may be 900ppm, 850ppm, 750ppm, or 700ppm. When the oxygen content R is in the range of 500 to 900ppm, the temperature rise of the battery during an external short circuit can be particularly suppressed.

[0037] It is preferable that the ratio Na / Nb of the number Na of the first zinc alloy particles to the number Nb of the second zinc alloy particles in the zinc alloy powder of the negative electrode is in the range of 10 / 90 to 90 / 10.

[0038] The ratio Na / Nb in the zinc alloy powder of the negative electrode can be 10 / 90 or more, 30 / 70 or more, 45 / 55 or more, or 50 / 50 or more. The ratio Na / Nb can be 90 / 10 or less, 75 / 25 or less, 67 / 33 or less, 55 / 45 or less, or 50 / 50 or less. The ratio Na / Nb can be in the range of 10 / 90 to 90 / 10, 30 / 70 to 90 / 10, 45 / 55 to 90 / 10, or 50 / 50 to 90 / 10. In any of these ranges, as long as the lower limit is not more than the upper limit, the upper limit can be 75 / 25, 67 / 33, 55 / 45, or 50 / 50.

[0039] In the zinc alloy powder of the negative electrode, the ratio Nc / Nt of the number Nc of the third zinc alloy particles to the total Nt of the number Na to the number Nb to the number Nc can be greater than 0 and less than 0.20. By setting it to this range, the rise in battery temperature during external short circuit can be suppressed. The ratio Nc / Nt can be greater than 0.02, greater than 0.04, greater than 0.10, or greater than 0.14. The ratio Nc / Nt can be less than 0.20, less than 0.14, or less than 0.10. The ratio Nc / Nt can be in the range of 0.02 to 0.20, 0.04 to 0.20, 0.10 to 0.20, or 0.14 to 0.20. In these ranges, as long as the lower limit is not greater than the upper limit, the upper limit can be 0.14 or 0.10.

[0040] In the alkaline dry battery (A), it is preferred that the ratio Na / Nb is within any of the above ranges, and the ratio Nc / Nt is within any of the above ranges.

[0041] The average particle size of the first to third particles can be independently 30 μm or more, 50 μm or more, 70 μm or more, or 90 μm or more, and can be 200 μm or less, 150 μm or less, or 125 μm or less. Here, the average particle size is the median particle size (D50) at which the cumulative volume in the volume-based particle size distribution is 50%. The median particle size is obtained using a dry laser diffraction / scattering particle size distribution measuring device.

[0042] From the viewpoint of suppressing the temperature rise during external short circuit, the average particle size of the first particles, the average particle size of the second particles, the average particle size of the third particles, and the average particle size of the zinc alloy powder as a whole can be in the range of 30 to 200 μm, 50 to 200 μm, 70 to 200 μm, or 90 to 200 μm, respectively. In any of these ranges, the upper limit can be 150 μm or 125 μm.

[0043] (Classification method of zinc alloy powder)

[0044] The method for classifying zinc alloy powder is described below. First, a cross-sectional image of the zinc alloy powder is obtained. The cross-sectional image is obtained, for example, by the following method. First, the zinc alloy powder is dispersed in a resin, and the resin is cured to obtain a sample. Next, at least a portion of the interior of the sample is exposed to expose the cross section of the zinc alloy powder. There is no limitation on the method for exposing the cross section, and a known method (such as a cross-sectional polishing machine method) can be used.

[0045] Next, an image of the exposed cross section is taken using a scanning microscope or the like to obtain a cross-sectional image. At this time, the image is obtained in a manner that more than 100 particles that are the subject of evaluation can be counted. As particles that are the subject of evaluation, particles with a maximum diameter of 10 μm or more in the cross-sectional image can be selected. Here, the maximum diameter refers to the maximum value of the straight-line distance between two points on the outer edge of the particle. Next, 100 particles that are the subject of evaluation are selected from the cross-sectional image, and the particles in the cross-sectional image are classified according to the following criteria.

[0046] (1) First particle (first zinc alloy particle)

[0047] The first particle is a particle having a specific hole H. In the hole H, the ratio D / W of the straight line distance D from the opening to the bottom surface to the width W of the opening is greater than 1.0. Furthermore, the straight line distance D is greater than 2 μm. It should be noted that particles having both holes H and holes V are classified as first particles. Holes that do not meet the above conditions contain uneven pits.

[0048] use Figure 1A The schematic diagram of the hole H is used to illustrate the identification method. It should be noted that, Figure 1A and Figure 1B In the figure, only a part of the particle 100 is shown. First, in the cross-sectional image of the zinc alloy particle 100, if there is a hole 110, the opening 111 of the hole is determined. Then, the width W of the opening 111 is calculated from the image. Next, the bottom surface 110b of the hole 110 is determined. The bottom surface 110b is the part of the inner surface of the hole 110 that is farthest from the opening 111. Then, the straight-line distance D (shortest distance) from the opening 111 to the bottom surface 110b is calculated from the image. Based on the calculated width W and straight-line distance D, it is determined whether the particle 100 belongs to the first particle.

[0049] (2) Second particle (second zinc alloy particle)

[0050] If the particle to be evaluated does not belong to the first particle, it is determined whether it belongs to the second particle. The second particle is a particle that does not have a specific hole H and has a specific hole V inside. The hole V is a hole with a short diameter of 2 μm or more and is not exposed outside the particle. Figure 1B The method for identifying hole V is explained with reference to the schematic diagram of FIG.

[0051] When a closed hole 120 is present in a zinc alloy particle 100, the short diameter of the hole 120 is determined. The short diameter refers to the maximum value of the diameter 120t of the hole 120 in a direction perpendicular to the maximum diameter 120m in the cross-sectional image of the particle. Whether the particle 100 is a second particle is determined based on the measured short diameter.

[0052] (3) Third particle (third zinc alloy particle)

[0053] When the particle to be evaluated does not belong to any of the first particle and the second particle, it is determined to be the third particle. In other words, the particle to be evaluated is classified as any of the first to third particles.

[0054] In the present application, the ratio of the first to third particles (particle number ratio) can be read as the ratio of the zinc alloy particles with a maximum diameter of 10 μm or more. When the average particle size of the zinc alloy powder (the first to third particles) is 10 μm or more, the classification result of the zinc alloy particles with a maximum diameter of 10 μm or more can be regarded as the classification result of the zinc alloy powder as a whole.

[0055] In addition, when evaluating the zinc alloy powder of the negative electrode in the battery, the battery in an unused (undischarged) state may be disassembled, and the zinc alloy powder may be taken out from the negative electrode for evaluation.

[0056] (Method for producing zinc alloy powder)

[0057] There is no limitation on the method for forming the zinc alloy powder, but preferably a rotating disk atomization method (centrifugal atomization method) is used. The rotating disk atomization method can simultaneously produce the first particle, the second particle, and the third particle by selecting conditions. That is, according to the rotating disk atomization method, a zinc alloy powder containing the first particle, the second particle, and the third particle can be produced through a single production process.

[0058] It should be noted that the target zinc alloy powder can also be produced by mixing a plurality of zinc alloy powders having different ratios of the first to third particles. For example, the target zinc alloy powder can be produced by mixing a zinc alloy powder mainly belonging to the first particle, a zinc alloy powder mainly belonging to the second particle, and a zinc alloy powder mainly belonging to the third particle at a specified ratio. In this case, the manufacturing methods of the zinc alloy powders can be the same or different. The zinc alloy powders can be produced by a rotating disk atomization method or by methods other than the rotating disk atomization method. Examples of methods other than the rotating disk atomization method include: a gas atomization method, or a composite atomization method that combines the gas atomization method and the rotating disk atomization method.

[0059] An example of the turntable atomization method (centrifugal atomization method) is described below. First, a zinc alloy is melted to obtain a melt. Next, the zinc alloy melt is dripped onto a rotating turntable in a chamber in the form of droplets, thereby obtaining a zinc alloy powder. The melt dripped onto the rotating turntable is scattered toward the wall of the chamber and cooled to become a zinc alloy powder. In the process of the melt being cooled on the turntable and in the chamber to become particles, the particle morphology (the ratio of the number of particles of the first to third particles) and the oxygen content R of the zinc alloy powder change according to the manufacturing conditions.

[0060] The configuration of the device used in the rotating disk atomization method (for example, the rotating disk) is not particularly limited, and a known device may be applied or a part of the known device may be modified and used.

[0061] By changing the drop speed of the melt, the rotation speed of the turntable and the atmosphere for manufacturing the powder (the atmosphere in the chamber), the shape of the particles (the formation state of the holes and pores) changes. By appropriately combining these conditions, the average particle size of the generated particles, the ratio of the first to third particles and the oxygen content R of the zinc alloy powder can be controlled. Regarding the atmosphere for manufacturing the powder, the oxygen concentration is important. By manufacturing the zinc alloy powder in an atmosphere containing oxygen, an oxide film is also formed on the inner surface of the pore V.

[0062] When the zinc alloy powder is produced by the rotating disk atomization method, it is preferable that at least one of the following conditions (1) to (3) is satisfied, and it is more preferable that two or all of the conditions are satisfied.

[0063] (1) The drop rate of the melt is in the range of 1.1 to 1.3 kg / min.

[0064] (2) The rotation speed of the turntable is in the range of 10000 to 15000 rpm.

[0065] (3) The oxygen concentration in the chamber is in the range of 10 to 15% by volume.

[0066] Among them, by setting the oxygen concentration in the chamber to a range of 10 to 15% by volume, the oxygen content R of the zinc alloy powder tends to increase. By reducing the rotation speed of the turntable or increasing the droplet speed of the melt, the particle size of the formed particles tends to become larger. By increasing the oxygen concentration in the chamber, the Na / Nb ratio tends to become higher. By reducing the oxygen concentration in the chamber, the proportion of the third particle tends to increase. Among them, these tendencies are affected by other manufacturing conditions, and therefore, depending on other manufacturing conditions, these tendencies are sometimes not observed.

[0067] When the chamber is replaced with an inert gas such as nitrogen and the oxygen concentration is controlled to be substantially 0% by volume, particles with a high degree of spheroidization can be produced. On the other hand, by performing the rotary disk atomization method in an atmosphere with an oxygen concentration higher than that of the conventional rotary disk atomization method, the ratio of the first and second particles is high, and a zinc alloy powder containing the first to third particles can be produced. Furthermore, by adjusting the drop speed and oxygen concentration of the melt, the ratio of the number of the first particles to the number of the second particles (ratio Na / Nb) can be controlled.

[0068] It should be noted that the oxide films present on the surfaces of the first to third particles are only oxide films due to natural oxidation. That is, the zinc alloy powder produced by the above production method is used for the production of negative electrodes without undergoing special additional treatments such as oxidation treatment (eg, chemical conversion treatment).

[0069] The alkaline dry battery (A) comprises a positive electrode, a negative electrode, a separator and an electrolyte, and may comprise other components as required. Examples of the configuration of the alkaline dry battery (A) are described below. The configuration of the alkaline dry battery (A) is not limited to the following examples. In the alkaline dry battery (A), known configurations may also be applied to configurations other than the characteristic configurations.

[0070] (negative electrode)

[0071] The negative electrode contains the above-mentioned zinc alloy powder as a negative electrode active material. Zinc alloy is an alloy of zinc and other metal elements. Other metal elements may include at least one selected from the group consisting of indium, bismuth and aluminum. The indium content in the zinc alloy may be in the range of 0.01 mass % to 0.1 mass %. The bismuth content in the zinc alloy may be in the range of 0.003 mass % to 0.02 mass %. The aluminum content in the zinc alloy may be in the range of 0.001 mass % to 0.03 mass %. From the viewpoint of corrosion resistance, the content of elements other than zinc in the zinc alloy may be in the range of 0.025 mass % to 0.08 mass %.

[0072] The first particles, the second particles, and the third particles typically have the same alloy composition, but may have different alloy compositions. Of the first to third particles, only two particles may have the same alloy composition.

[0073] The negative electrode may be a gel-like negative electrode. The gel-like negative electrode may be prepared, for example, by mixing negative electrode active material particles, a gelling agent, and an alkaline electrolyte. As the gelling agent, a known gelling agent used in the field of alkaline dry batteries may be used. For example, a water-absorbing polymer or the like may be used as the gelling agent. Examples of the gelling agent include polyacrylic acid, sodium polyacrylate, and the like. The amount of the gelling agent may be in the range of 0.5 to 2.5 parts by mass per 100 parts by mass of the negative electrode active material (zinc alloy powder).

[0074] A surfactant may also be added to the negative electrode to improve the reaction efficiency on the surface of the negative electrode active material. For example, a polyoxyalkylene-containing compound, a phosphate ester, etc. may be used as the surfactant. From the viewpoint of making the additive more uniformly dispersed in the negative electrode, the additive is preferably added in advance to the alkaline electrolyte used in the preparation of the negative electrode.

[0075] A compound containing a metal having a high hydrogen overvoltage, such as indium or bismuth, may be appropriately added to the negative electrode to improve corrosion resistance.

[0076] (Negative Electron Collector)

[0077] The alkaline dry cell (A) may include a negative electrode collector embedded in the negative electrode. The material of the negative electrode collector may be a metal (single metal or alloy). The material of the negative electrode collector preferably includes copper, or may be an alloy including copper and zinc (e.g., brass). The negative electrode collector may be plated with tin or the like as needed.

[0078] (positive electrode)

[0079] There is no particular limitation on the positive electrode, and a known positive electrode can be used. The positive electrode contains manganese dioxide as a positive electrode active material. The positive electrode usually contains a positive electrode active material and a conductive material, and further contains a binding material as needed. The positive electrode can be formed by pressurizing the positive electrode mixture into a cylindrical body (positive electrode pellets). The positive electrode mixture, for example, contains a positive electrode active material, a conductive material, an alkaline electrolyte, and further contains a binding material as needed. After the cylindrical body is housed in the shell body, it can be pressurized in a manner that is closely fitted to the inner wall of the shell body.

[0080] A preferred example of manganese dioxide as the positive electrode active material is electrolytic manganese dioxide, but natural manganese dioxide and chemical manganese dioxide can also be used. As the crystal structure of manganese dioxide, α-type, β-type, γ-type, δ-type, ε-type, η-type, λ-type, and ramsdellite type can be cited.

[0081] The conductive material may be a conductive carbon material. Examples of the conductive carbon material include carbon black (such as acetylene black) and graphite. Examples of graphite include natural graphite and artificial graphite. The conductive material may be used in powder form.

[0082] In order to absorb hydrogen generated inside the battery, a silver compound may be added to the positive electrode. Examples of the silver compound include silver oxide (Ag2O, AgO, Ag2O3, etc.), silver nickel composite oxide (AgNiO2), and the like.

[0083] (Separator)

[0084] There is no particular limitation on the separator, and a known separator can be used. Examples of the form of the separator include nonwoven fabrics, microporous films, etc. Examples of the material of the nonwoven fabric include cellulose, polyvinyl alcohol, polyolefins, etc. The nonwoven fabric can be formed by mixing different fibers. Examples of the material of the microporous film include cellophane, polyolefins, etc. The thickness of the separator can be in the range of 200μm to 300μm. Multiple separators can be overlapped and used.

[0085] (Battery housing)

[0086] There is no particular limitation on the battery casing, and a casing that conforms to the shape of the battery can be used. There is no particular limitation on the shape of the alkaline dry cell (A), and it can be cylindrical or coin-shaped (including button-shaped). The battery casing generally includes a battery case, a negative terminal plate, and a gasket. A metal casing, for example, a cylindrical metal casing with a bottom is used in the battery case. The metal casing can be a casing formed of a nickel-plated steel plate. In order to reduce the contact resistance between the positive electrode and the battery casing, the inner surface of the battery casing can be covered with a carbon coating. The negative terminal plate can be formed of the same material as the metal casing, or it can be formed of a nickel-plated steel plate.

[0087] Examples of the material of the gasket include polyamide, polyethylene, polypropylene, etc. The gasket can be formed, for example, by injection molding the above materials into a predetermined shape. Examples of the material of the gasket include polyamide-6,6, polyamide-6,10, polyamide-6,12, polypropylene, etc.

[0088] (Alkaline electrolyte)

[0089] There is no particular limitation on the alkaline electrolyte, and a known alkaline electrolyte can be used. As the alkaline electrolyte, for example, an alkaline aqueous solution containing potassium hydroxide is used. The concentration of potassium hydroxide in the alkaline electrolyte is preferably in the range of 30 to 50% by mass (for example, in the range of 30 to 40% by mass). The alkaline electrolyte may also contain lithium hydroxide (LiOH), sodium hydroxide (NaOH), cesium hydroxide (CsOH), rubidium hydroxide (RbOH), etc.

[0090] The alkaline electrolyte may contain a surfactant. By using a surfactant, the reaction efficiency between the negative electrode active material particles and the electrolyte can be improved. The surfactant may be the substance exemplified in the negative electrode. The content of the surfactant in the alkaline electrolyte is usually in the range of 0 to 0.5 mass % (e.g., 0 to 0.2 mass %).

[0091] (Method for manufacturing alkaline dry cell)

[0092] The method for producing the alkaline dry battery (A) using the zinc alloy powder is not particularly limited, and a known production method can be applied. For example, the production method described in the Examples can be used.

[0093] Hereinafter, an example of an embodiment of the present disclosure will be described in detail with reference to the accompanying drawings. The above-mentioned constituent elements can be applied to the constituent elements of the example described below. In addition, the constituent elements of the example described below can be changed based on the above description. The constituent elements that are not essential for the alkaline dry cell (A) can be omitted from the constituent elements of the example described below. In addition, the matters described below can be applied to the above-mentioned embodiment.

[0094] (Implementation Method 1)

[0095] A partially exploded cross-sectional view of the alkaline dry battery 10 according to the first embodiment is shown in Figure 2 The alkaline dry battery 10 is a cylindrical battery having an inside-out structure. The alkaline dry battery 10 comprises a battery case 1, a positive electrode 2, a negative electrode (gel-like negative electrode) 3, a separator 4, a sealing unit 9 and an alkaline electrolyte (not shown). The positive electrode 2, the negative electrode 3, the separator 4 and the alkaline electrolyte are arranged in the battery case 1 (inside the battery shell). The negative electrode 3 comprises the above-mentioned zinc alloy powder.

[0096] The battery case 1 is a bottomed cylindrical case and functions as a positive electrode terminal. The positive electrode 2 is a hollow cylindrical case and is arranged in contact with the inner wall of the battery case 1. The negative electrode 3 is arranged in the hollow part of the positive electrode 2. The separator 4 is arranged between the positive electrode 2 and the negative electrode 3.

[0097] The separator 4 is composed of a cylindrical separator 4a and a liner 4b. The separator 4a is arranged along the inner surface of the hollow portion of the positive electrode 2 to separate the positive electrode 2 from the negative electrode 3. The liner 4b is arranged at the bottom of the hollow portion of the positive electrode 2 to separate the negative electrode 3 from the battery case 1.

[0098] The opening of the battery case 1 is sealed by a sealing unit 9. The sealing unit 9 includes a gasket 5, a negative electrode collector 6, and a negative electrode terminal plate 7. The negative electrode terminal plate 7 functions as a negative electrode terminal. The negative electrode collector 6 has a nail shape having a head and a main body. The main body of the negative electrode collector 6 is embedded in the through hole provided in the central part of the gasket 5 and embedded in the negative electrode 3. The head of the negative electrode collector 6 is welded to the flat portion in the center of the negative electrode terminal plate 7.

[0099] The opening end of the battery case 1 is fitted to the periphery (flange) of the negative terminal plate 7 via the periphery of the gasket 5. The outer surface of the battery case 1 is covered with an exterior label 8. The battery case 1, gasket 5 and negative terminal plate 7 constitute a battery casing.

[0100] Example

[0101] Hereinafter, the present disclosure will be specifically described based on examples, but the present disclosure is not limited to the following examples. In the following examples, a plurality of alkaline dry batteries having different negative electrodes were produced and evaluated.

[0102] (Battery A1)

[0103] Follow the steps below to create a Figure 2 The shape shown is a single 3-shaped cylindrical alkaline dry cell (LR6).

[0104] (1) Preparation of positive electrode

[0105] Graphite powder (conductive agent, average particle size: 8 μm) is added to the electrolytic manganese dioxide powder to obtain a mixture. The mass ratio of the electrolytic manganese dioxide powder to the graphite powder is set to (electrolytic manganese dioxide powder): (graphite powder) = 92.4:7.6. 1.5 parts by mass of the electrolyte is added to 100 parts by mass of the obtained mixture and stirred thoroughly, and then compressed into flakes to obtain a positive electrode mixture. In the electrolyte, an alkaline aqueous solution containing potassium hydroxide and zinc oxide is used. In the alkaline aqueous solution, the concentration of potassium hydroxide is set to 35% by mass and the concentration of zinc oxide is set to 2% by mass.

[0106] The flaky positive electrode mixture was pulverized into particles, which were classified using a 10-100 mesh sieve, and the classified particles were press-formed into a predetermined hollow cylindrical shape to prepare two positive electrode pellets (positive electrodes).

[0107] (2) Preparation of negative electrode

[0108] The zinc alloy powder was prepared by a rotating disk atomization method. Specifically, first, a zinc alloy was melted to form a melt. The zinc alloy used was a zinc alloy containing 0.02 mass % of indium, 0.01 mass % of bismuth, and 0.005 mass % of aluminum.

[0109] Next, a zinc alloy melt was dripped onto a rotating turntable in an atmosphere having an oxygen concentration of 10% by volume. Thus, a zinc alloy powder was obtained. The dripping rate of the zinc alloy melt was set to 1.1 kg / min. The rotation speed of the turntable was set to 10,000 rpm. The obtained zinc alloy powder was evaluated by the method described below.

[0110] The obtained zinc alloy powder (negative electrode active material) is mixed with an electrolyte and a gelling agent to obtain a gelled negative electrode. The electrolyte used is the same electrolyte used in the preparation of the positive electrode pellets. The gelling agent used is a mixture of cross-linked branched polyacrylic acid and highly cross-linked chain type sodium polyacrylate. The mass ratio of zinc alloy powder to electrolyte and gelling agent is set to (zinc alloy powder): (electrolyte): (gelling agent) = 100:50:1.

[0111] (3) Assembly of alkaline dry batteries

[0112] First, a carbon coating (thickness: about 10 μm) is formed on the inner surface of a bottomed cylindrical shell (outer diameter 13.80 mm, height 50.3 mm) to obtain a shell 1. A shell made of a nickel-plated steel plate is used in the shell. Next, after two positive electrode pellets are embedded in the shell 1 in the longitudinal direction, pressurization is performed to form a positive electrode 2 that is closely attached to the inner wall of the shell 1. Next, a bottomed cylindrical separator 4 is arranged on the inner side of the positive electrode pellets. The separator 4 is composed of a cylindrical separator 4a and a backing paper 4b. What is used in the cylindrical separator 4a and the backing paper 4b is a non-woven fabric sheet mainly composed of rayon fibers and polyvinyl alcohol fibers. The separator 4a is formed by winding a triple non-woven fabric sheet.

[0113] Next, an electrolyte is injected into the housing 1, and the electrolyte is impregnated into the separator 4. The electrolyte used is the same electrolyte used in the preparation of the positive electrode pellets. The housing 1 injected with the electrolyte is left for a predetermined time to allow the electrolyte to penetrate from the separator 4 to the positive electrode 2. Thereafter, a predetermined amount of gelled negative electrode (negative electrode 3) is filled inside the separator 4.

[0114] The negative electrode collector 6 is obtained as follows: after pressing and processing general brass (Cu content: about 65 mass%, Zn content: about 35 mass%) into a nail shape, tinning is applied to the surface. The head of the negative electrode collector 6 is welded to the negative terminal plate 7 made of nickel-plated steel plate. Thereafter, the main body of the negative electrode collector 6 is pressed into the through hole of the resin gasket 5. In this way, a sealing unit 9 formed by the gasket 5, the negative terminal plate 7 and the negative electrode collector 6 is made.

[0115] Next, the sealing unit 9 is arranged at the opening of the housing 1. At this time, the main body of the negative electrode current collector 6 is embedded in the negative electrode 3. Next, the opening end of the housing 1 is fitted to the peripheral edge of the negative electrode terminal plate 7 by means of the gasket 5, and the opening of the housing 1 is sealed. Next, the outer surface of the housing 1 is covered with the exterior label 8. In this way, the battery A1 (alkaline dry battery) is manufactured.

[0116] (Batteries A2~A8 and X1~X4)

[0117] Various types of zinc alloy powders were produced in the same manner as the production method described in (2) above, except that the production conditions were changed as shown in Table 1. The obtained zinc alloy powders were evaluated by the method described below.

[0118] A plurality of batteries (batteries A2 to A8 and X1 to X4) were produced in the same manner as battery A1 except that the obtained zinc alloy powder was used as a negative electrode active material.

[0119] (Evaluation of zinc alloy powder)

[0120] (1) Evaluation of oxygen content R

[0121] The oxygen content R (mass ratio) of the zinc alloy powder was measured using an oxygen / nitrogen gas analyzer EMGA-Pro manufactured by Horiba, Ltd., according to the IGA (Instrumental Gas Analysis) method.

[0122] (2) Evaluation of the ratio of the first to third particles

[0123] The prepared zinc alloy powder is classified by the following method. First, the zinc alloy powder is dispersed in a resin, and the resin is solidified to obtain a sample. Then, the cross section of the sample is exposed by a cross section polisher method. Then, the exposed cross section is photographed with a scanning microscope to obtain an image containing more than 100 particles to be evaluated (particles with a maximum diameter of 10 μm or more in the cross section image).

[0124] 100 particles with a maximum diameter of 10 μm or more contained in the obtained image are randomly selected and evaluated according to the above criteria as to which of the first to third particles they belong to. Then, the above ratio Na / Nb and the particle number ratio of the first to third particles are obtained from the evaluation results.

[0125] (3) Evaluation of average particle size

[0126] The average particle size (D50) of the prepared zinc alloy powder was measured. The average particle size can be determined by measuring the volume-based particle size distribution by dry dispersion using Mastersizer 3000 (manufactured by Malvern Panalytical), which is a laser diffraction particle size distribution analyzer.

[0127] (Battery Evaluation)

[0128] The prepared battery was evaluated by the following method. First, the positive terminal and negative terminal of the battery were externally short-circuited using a nickel tab. At this time, the surface temperature of the central part of the side of the battery was monitored to determine the maximum temperature T (°C) during the external short-circuit.

[0129] Part of the production conditions of the zinc alloy powder, the evaluation results of the powder, and the evaluation results of the battery are shown in Table 1. It should be noted that batteries A1 to A8 are alkaline dry batteries (A) of the present disclosure, and X1 to X4 are batteries of comparative examples.

[0130] [Table 1]

[0131]

[0132] As shown in Table 1, the maximum temperature T during external short circuit is significantly reduced in Batteries A1 to A8 of the present disclosure. As shown in Table 1, the oxygen content R of the zinc alloy powder is in the range of 400 to 1000 ppm, which can suppress the temperature rise of the battery during external short circuit.

[0133] Industrial Applicability

[0134] The present disclosure can be applied to alkaline dry batteries.

[0135] The present invention has been described with respect to the presently preferred embodiments, but such disclosure is not to be construed in a limiting sense. Various modifications and changes should be apparent to those skilled in the art in the art to which the present invention belongs by reading the above disclosure. Therefore, the appended claims should be construed to include all modifications and changes without departing from the spirit and scope of the present invention.

[0136] Description of Reference Numerals

[0137] 1: Battery housing

[0138] 2: Positive electrode

[0139] 3: Negative electrode

[0140] 4: Separator

[0141] 5: Gasket

[0142] 9: Sealing unit

[0143] 10: Alkaline dry batteries.

Claims

1. An alkaline dry battery comprising: a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, The negative electrode comprises zinc alloy powder, The zinc alloy powder comprises first zinc alloy particles, second zinc alloy particles and third zinc alloy particles. In the cross-sectional image of the zinc alloy powder, The first zinc alloy particles are particles having specific pores. The second zinc alloy particles are particles that do not have the specific pores and have specific closed pores inside. The third zinc alloy particles are particles that do not have the specific pores and do not have the specific closed pores inside. The specific hole is a hole in which a ratio D / W of a straight line distance D from the opening to the bottom surface to a width W of the opening is 1.0 or more, and the straight line distance D is 2 μm or more. The specific closed pores are pores with a short diameter of 2 μm or more. The oxygen content of the zinc alloy powder is in the range of 400 to 1000 ppm by mass ratio.

2. The alkaline dry battery according to claim 1, wherein The oxygen content of the zinc alloy powder is in a range of 500 to 900 ppm by mass.